IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KEPARIWISATAAN DI DESA OLELE KABUPATEN BONE BOLANGO - Ni Kadek Putri Widyaningtyas Tirta; Ismet Sulila; Rusli Isa (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to find out and describe Implementation of Tourism Development Policies in Olele Village, Bone Bolango Regency and the Factors that influence the Implementation of Tourism Development Policies. The research method used is descriptive qualitative, using data collection techniques through interviews, observation and documentation studies. The data analysis technique uses the Miles Huberman model with the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study found that the Implementation of Tourism Development Policies in Olele Village, Bone Bolango Regency, has been going well in terms of planning which has used ecological studies. The implementation has been running quite well in accordance with the planning. The Regular monitoring and evaluation is carried out. However, in its implementation there are still several obstacles.The obstacle lies in the communication factor where there is still a lack of coordination and tourism promotion. Insufficient resource management. As well as the Disposition orthe implementor behavior where problems arise from community who do not yet have compliance in the effort to implement tourism development policies in Olele Village. However, the distribution of authority and tourism CSR also the SOP has been carried out properly.